Learning Management Innovation at Tumpaan Vocational School - Rima Fien Lolong; Deitje Adolfien Katuuk; Jeffry Lengkong; Viktory Nikodemus Joufree Rotty (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study aims to analyze and describe learning management innovations at Tumpaan State Vocational School. This study uses qualitative research methods with reference to Creswell that qualitative research is research in which the form of data is in the form of words or interview results and not in the form of statistical calculations. Innovation in learning management at the Tumpaan State Vocational High School was carried out through instilling character education with a routine worship program which was carried out once a week. In carrying out innovations related to learning management at the Tumpaan State Vocational School, it focuses on management functions consisting of planning, implementation, monitoring and evaluation. While at the implementation stage the scheduling of worship once a week is carried out by rotating the picket or person in charge of worship activities, supervision is carried out by monitoring the activities of teachers and students for one period to find out how far this program has been implemented and evaluation is carried out by scheduling students to practice leading worship both sermons and prayer.